One-step hydrothermal synthesis and photocatalytic activity of SnO\(_2\)/rGO nanocomposites: effects of pH values - Pham, Van Tuan; Hoang, Ba Tuong; Tran, Ngoc Khiem (Communications in Physics, 2021)
In this study, tin oxide /reduced graphene oxide (SnO2/rGO) samples were prepared by hydrothermal method. The structural characteristics, phase composition, morphology, and size of the samples were studied by X-ray diffraction, Raman scattering spectroscopy, and scanning electron microscopy. Results showed that SnO2 nanoparticles had tetragonal rutile crystal structure with a size ranging from 4.65 nm to 5.77 nm when the pH was increased from 5 to 9. The SnO2 nanoparticle morphology together with rGO layers was observed in the FESEM image of these samples. The absorption spectra of SnO2/rGO samples show the characteristic absorption peak of SnO2 at 296 nm, in which the band gap value of the material decreased from 3.91 eV to 3.81 eV when pH was increased from 5 to 9. The simultaneous formation of the two phases of SnO2 and rGO was demonstrated by Raman scattering spectroscopy. Photocatalytic degradation of methylene blue reached 86% after 90 min under visible light.